PROSPECTS FOR THE DEVELOPMENT OF FORENSIC EXAMINATION IN THE CONTEXT OF SCIENTIFIC AND TECHNOLOGICAL PROGRESS - Abdullaev Rustam Kahramanovich (International Journal of Business, Law and Political Science, 2024)
Objective: This study examines how forensic examination has developed as a scientific field in the face of swift scientific and technological breakthroughs, with a focus on improving techniques and technical instruments. Method: Recent advancements in forensic equipment and the scientific foundation of new approaches were systematically reviewed. The analysis emphasizes advancements in object detection, data administration, and assessment procedures while highlighting the importance of expert competency in line with certain credentials. Results: There have been notable developments in forensic technology, such as new tools and methodological enhancements that raise the accuracy and dependability of tests. Contentious issues are rigorously analyzed, including inconsistent language, financial difficulties, and the upkeep of sophisticated machinery. Novelty: The study presents novel approaches to systematizing forensic data and highlights the necessity of scientifically proven methods, highlighting the vital role of expert qualifications in the research process. It also emphasizes opportunities for future progress in forensic examination as both a scientific discipline and a practical application field.